Factors Affecting Career Success of Employees in the Insurance Sector of Pakistan - Pasha, Ahmad Tisman; Hamid, Dr. Kamal bin Ab; Shahzad, Dr. Arfan (Advances in Social Sciences Research Journal, 2016)
Present article focuses on the key factors having influence on career success of employees in the insurance sector of Pakistan. We proposed an evolving process of career success and career commitment of working employees of insurance sector of Pakistan. It is found that career development practices like promotional opportunity, rewards, job security and training play vital role to build career commitment and career success of working employees of insurance sector